2009
DOI: 10.1103/physrevb.80.214534
|View full text |Cite
|
Sign up to set email alerts
|

Phonons in doped and undopedBaFe2As2investigated by inelastic x-ray scattering

Abstract: We measured phonon frequencies and linewidths in doped and undoped BaFe 2 As 2 single crystals by inelastic x-ray scattering and compared our results with density functional theory calculations. In agreement with previous work, the calculated frequencies of some phonons depended on whether the ground state was magnetic or not and, in the former case, whether phonon wave vector was parallel or perpendicular to the magnetic ordering wave vector. The experimental results agreed better with the magnetic calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
57
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 22 publications
16
57
3
Order By: Relevance
“…The presence of only small changes in phonon spectra resulting from either temperature or doping, is in agreement with work by many other authors using various methods including IXS and inelastic neutron scattering, [14][15][16] nuclear resonant inelastic scattering, 17) Raman, 18) and infrared spectroscopy. 19) The discrepancies exists between the observed data and the ab-initio calculations is smaller in the 'magnetic' calculation than the 'original' non-magnetic one.…”
Section: Discussionsupporting
confidence: 76%
“…The presence of only small changes in phonon spectra resulting from either temperature or doping, is in agreement with work by many other authors using various methods including IXS and inelastic neutron scattering, [14][15][16] nuclear resonant inelastic scattering, 17) Raman, 18) and infrared spectroscopy. 19) The discrepancies exists between the observed data and the ab-initio calculations is smaller in the 'magnetic' calculation than the 'original' non-magnetic one.…”
Section: Discussionsupporting
confidence: 76%
“…This E g mode is a doubly-degenerate mode impacting Fe and As, and the contention is that the split is too large to be accounted for by the orthorhombic distortion and instead is indicative of spin-phonon coupling. Measurements of phonon behavior conducted with inelastic x-ray spectroscopy are replicated well by theory when magnetism is explicitly taken into account 34 , indicating the presence of spinphonon coupling.…”
mentioning
confidence: 56%
“…Since the acoustic phonon frequency goes as the square root of the elastic constant, we expect a softening of the lowenergy acoustic phonon modes of BaFe 2 As 2 when passing through the structural transition temperature. Phonon calculations predict a linear dispersion in the low-energy, long wavelength regime 30,34 . The acoustic phonon modes in BaFe 2 As 2 can be characterized with energy transfers of less than 10 meV, and the small and constant momentum resolution offered by IXS allows precise measurements of the phonon dispersion as a function of temperature.…”
mentioning
confidence: 99%
“…[38]. It was later shown that the inclusion of a static AFM order leads indeed to a softening the Fe-As spring constant, and improves the agreement of the predicted crystal structure and phonon frequencies with experiment [42]; however, this cannot explain the softening of c-polarized As modes, which form a distinct peak at 20 meV, at an energy 20 % lower than predicted by calculations, which has been observed both in 1111 and 122 samples, and has been attributed to anomalous e − ph coupling [39,41].…”
Section: Discussionmentioning
confidence: 86%